Annotated catalogue of the click-beetle subfamily Tetralobinae (Coleoptera: Elateridae) - Kubaczkova, Magdalena; Kundrata, Robin (Zootaxa, 2017)
An annotated catalogue of the World Tetralobinae (Coleoptera: Elateridae) is presented. Two tribes are recognized, Tetralobini and Piezophyllini. Altogether, 78 species are classified in Tetralobinae. Tetralobini includes 73 species in six genera: Tetralobus Lepeletier & Audinet-Serville, 1828 (52 species; subgenus Tetralobus 51 species, subgenus Dodecamerus Laurent, 1968 one species), Neotetralobus Girard, 1987 (one species), Paratetralobus Laurent, 1964a (one species), Pseudalaus Laurent, 1967 (two species), Pseudotetralobus Schwarz, 1902 (16 species), and Sinelater Laurent, 1967 (one species). Piezophyllini includes only Piezophyllus Hope, 1842 (five species). Most Tetralobinae are distributed in the Afrotropical Region, and several species are additionally known from the Oriental, East Palaearctic, and Australian Regions. For each taxon we provide synonyms, information on types, type localities, distribution, and bibliography. Sinelater perroti (Fleutiaux, 1940) is recorded from Bhutan for the first time.